Labor mobility : an enabler for sustainable development - Labor Mobility an Enabler for Sustainable Development Abu Dhabi 2013; Omelaniuk, Irena; Al-Noaimi, Ali Rashid; Emirates Center for Strategic Studies and Research (Abu Dhabi The Emirates Center for Strategic Studies and Research (ECSSR), 2013)
​Labor mobility is particularly significant in the case of the GCC; the region is host to around 15 million expatriate workers who generate US $80 billion in annual remittances each year and support an estimated 150 million dependents in their various home countries. However, little research has been conducted to identify and measure the impacts of this phenomenon on migrants’ host countries or countries of origin. Therefore, with a view to contributing to the active engagement of GCC countries in the global dialogue on migration and development, the Emirates Center for Strategic Studies and Research (ECSSR) hosted a special conference, Labor Mobility: Enabler for Sustainable Development, in Abu Dhabi on May 14–15, 2013. The Conference was held under the patronage of H.H. Sheikh Mansour Bin Zayed Al Nahyan, UAE Deputy Prime Minister and Minister of Presidential Affairs, and was jointly organized by the Ministry of Foreign Affairs, the Ministry of Labor, the ECSSR and the National Qualification Authority. It was convened in association with the GCC Council of Ministers of Labor, the Government of Sweden – current Chair of the Global Forum on Migration and Development (GFMD) – the International Organization for Migration and the World Bank. The papers presented at the Conference, compiled in this volume, provide a variety of informed views on labor mobility as an enabler for human, economic and social development. They explore migration policy and governance in the GCC states; the potential for research collaboration between migrant-sending and -receiving countries; the impact of Indian labor migration to the GCC states; the relationship between remittances and economic cycles in home and host countries; and the implications of labor mobility for families and households.
Introduction: Labor mobility: a regional debate for global solutions / Ali Rashid Al-Noaimi, Irena Omelaniuk -- 1. The development impacts of temporary migration and the protection vs. opportunities trade-off / David Mckenzie -- 2. The economic development benefits of human mobility to source countries / Yaw Nyarko -- 3. The effects of remittances / George Naufal and Ismail H. Genc -- 4. Recessions and remittances in home and host countries: an overview / Serdar Sayan -- 5. Seize the spotlight: a case for GCC engagement in research on the effects of labor migration / Michael Clemens -- 6. Migration policy and governance in the GCC: a regional perspective / Zabra Babar -- 7. Optimizing benefits from labor mobility: the case for research collaboration between Bangladesh and the GCC / C.R. Abrar -- 8. Drivers of development: the impact of Indian labor migration to the GCC / S. Irudaya rajan
Include bibliographical references (P: 239-260) and index
Keywords: Labour market; LABOUR MOBILITY; MIGRATION; SUSTAINABLE DEVELOPMENT; REMITTANCES; ECONOMIC RECESSION; CONFERENCE PAPERS; Gulf Cooperation Council